Tolerability and Pharmacokinetics of Ingenol Mebutate 0.05% Gel Applied to Treatment Areas up to 100cm(2) on the Forearm(s) of Patients with Actinic Keratosis - Anderson, Lawrence (J Clin Aesthet Dermatol, 2014)
Objective: To determine safety, tolerability, and systemic absorption of ingenol mebutate 0.05% gel applied for two consecutive days to treatment areas up to 100cm(2) on the forearm(s) of patients with actinic keratosis. Design and setting: Two studies are reported: a Phase 1, multicenter, open-label, dose-area escalation cohort study (http://www.clinicaltrials.gov/ct2/show/NCT00659893) and a Phase 2, double-blind, vehicle-controlled pharmacokinetic study (http://clinical trials.gov/ct2/show/NCT00852137). Participants: The Phase 1 study included male patients (n=65), mean age 68.1 years; the Phase 2 study included both male and female patients (n=16), mean age 63.3 years. Measurements: In the Phase 1 study, patients assigned to escalating dose-area cohorts were evaluated for local skin responses, adverse events, and any other relevant safety data. In the pharmacokinetic study, blood samples were collected pre-dose and for up to 24 hours after administration on Day 2, and analyzed for ingenol mebutate and its primary metabolites. In both studies, safety assessments were performed on Days 2, 3, 8, 15, 29, and 57 (study end). Results: In the Phase 1 study, most adverse events were mild, and all treatment-related adverse events resolved before the end of the study. The 100cm(2) treatment area showed a small increase in the overall intensity of mean composite local skin response scores. There was no quantifiable systemic exposure to ingenol mebutate or its primary metabolites. Conclusion: Ingenol mebutate 0.05% gel has a good safety profile when applied to treatment areas up to 100cm(2) with acceptable tolerability and local skin responses. There is no systemic absorption following application to areas of 100cm(2).